Moral distress in rural veterinarians as an outcome of the Mycoplasma bovis incursion in southern New Zealand. Issue 3 (4th May 2023) - Doolan-Noble, F; Noller, G; Jaye, C; Bryan, M
ABSTRACT : Aims: To gain insight into the world of rural veterinarians during the Mycoplasma bovis incursion within southern Aotearoa New Zealand by exploring their experiences during the incursion, and to understand the consequences, positive and negative, of these experiences. Methods: A qualitative social science research methodology, guided by the philosophical paradigm of pragmatism, was used to collect data from an information-rich sample (n = 6) of rural veterinarians from Otago and Southland. Interview and focus group techniques were used, both guided by a semi-structured interview guide. Veterinarians were asked a range of questions, including their role within the incursion; whether their involvement had any positive or negative impact for them; and their experience of conflicting demands. Analysis of the narrative data collected was guided by Braun and Clarke's approach to reflexive thematic analysis. Results and findings: All six participants approached agreed to participate. Analysis of the data provided an understanding of the trauma they experienced during the incursion. An overarching theme of psychological distress was underpinned by four sub-themes, with epistemic injustice and bearing witness the two sub-themes reported to be associated with the greatest experience of psychological distress. These, along with the other two identified stressors, led to the experience of moral distress, with moral residue and moral injury also experienced by some participants. Conclusions: Eradication programmes for exotic diseases in production animals inevitably have an impact on rural veterinarians, in their role working closely with farmers. Potentially, these impacts could be positive, recognising and utilising veterinarians' experience, skills and knowledge base. This study, however, illustrates the significant negative impacts for some rural veterinarians exposed to the recent M. bovis eradication programme in New Zealand, including experiences of moral distress and moral injury. Consequently, this eradication programme resulted in increased stress for study participants. There is a need to consider how the system addresses future exotic disease incursions to better incorporate and utilise the knowledge and skills of the expert workforce of rural veterinarians and to minimise the negative impacts on them. Clinical relevance: To date, the experience of moral distress by rural veterinarians during exotic disease incursions has been under-reported globally and unexplored in New Zealand. The findings from this study contribute further insights to the existing limited literature and provide guidance on how to reduce the adverse experiences on rural veterinarians during future incursions. Abbreviations: MPI: Ministry for Primary Industries; PITS: Perpetration-induced traumatic stress; PTSD: Post-traumatic stress disorder.